Comparative and transnational history: Central European approaches and new perspectives - Haupt, Heinz-Gerhard; Kocka, Jürgen (Berghahn Books, 2009)
Comparison and beyond : traditions, scope, and perspective of comparative history / Jürgen Kocka/Heinz-Gerhard Haupt -- The debate between comparison and transfers--and what now? / Hartmut Kaelble -- A "transnational" history of society : continuity or new departure / Jürgen Osterhammel -- Double marginalization : a plea for a transnational perspective on German history / Sebastian Conrad -- Entangled histories of uneven modernities : civil society, caste councils, and legal pluralism in postcolonial India / Shalini Randeria -- Lost in translation? Transcending boundaries in comparative history / M. Juneja, M. Pernau -- The nation as a developing resource community : a generalizing comparison / Dieter Langewiesche -- Birds of a feather : a comparative history of German and U.S. labour in the nineteenth and twentieth centuries / Thomas Welskopp -- Common challenges, common solutions? Visions of the future during the 1960s : GDR, CSSR, and the Federal Republic of Germany in comparative perspective / Jürg Requate -- Comparisons, cultural transfers, and the study of networks : towards a transnational history of Europe / Philipp Ther -- Germany and Africa in the late nineteenth and twentieth centuries : an entangled history? / Andreas Eckert -- Losing national identity or gaining transcultural competence : changing approaches in migration history / Dirk Hoerder